Preparation, Biodistribution and Neurotoxicity of Liposomal Cisplatin following Convection Enhanced Delivery in Normal and F98 Glioma Bearing Rats - Huo, Tianyao; Barth, Rolf F.; Yang, Weilian; Nakkula, Robin J.; Koynova, Rumiana; Tenchov, Boris; Chaudhury, Abhik Ray; Agius, Lawrence; Boulikas, Teni; Elleaume, Helene; Lee, Robert J. (PLOS ONE, 2012)
The purpose of this study was to evaluate two novel liposomal formulations of cisplatin as potential therapeutic agents for treatment of the F98 rat glioma. The first was a commercially produced agent, Lipoplatin™, which currently is in a Phase III clinical trial for treatment of non-small cell lung cancer (NSCLC). The second, produced in our laboratory, was based on the ability of cisplatin to form coordination complexes with lipid cholesteryl hemisuccinate (CHEMS). The in vitro tumoricidal activity of the former previously has been described in detail by other investigators. The CHEMS liposomal formulation had a Pt loading efficiency of 25% and showed more potent in vitro cytotoxicity against F98 glioma cells than free cisplatin at 24 h. In vivo CHEMS liposomes showed high retention at 24 h after intracerebral (i.c.) convection enhanced delivery (CED) to F98 glioma bearing rats. Neurotoxicologic studies were carried out in non-tumor bearing Fischer rats following i.c. CED of Lipoplatin™ or CHEMS liposomes or their “hollow” counterparts. Unexpectedly, Lipoplatin™ was highly neurotoxic when given i.c. by CED and resulted in death immediately following or within a few days after administration. Similarly “hollow” Lipoplatin™ liposomes showed similar neurotoxicity indicating that this was due to the liposomes themselves rather than the cisplatin. This was particularly surprising since Lipoplatin™ has been well tolerated when administered intravenously. In contrast, CHEMS liposomes and their “hollow” counterparts were clinically well tolerated. However, a variety of dose dependent neuropathologic changes from none to severe were seen at either 10 or 14 d following their administration. These findings suggest that further refinements in the design and formulation of cisplatin containing liposomes will be required before they can be administered i.c. by CED for the treatment of brain tumors and that a formulation that may be safe when given systemically may be highly neurotoxic when administered directly into the brain.